Efficacy of a sequential treatment strategy with GEMOX-based followed by FOLFIRI-based chemotherapy in advanced biliary tract cancers. (2nd October 2016) - Sebbagh, Sihem; Roux, Julia; Dreyer, Chantal; Neuzillet, Cindy; de Gramont, Armand; Orbegoso, Cecilia; Hentic, Olivia; Hammel, Pascal; de Gramont, Aimery; Raymond, Eric; André, Thierry; Chibaudel, Benoist; et al.
Abstract: Background: Gemcitabine (GEM)-platinum chemotherapy stands as first-line therapy for patients with recurrent/advanced biliary tract cancer (BTC), yielding progression-free survival (PFS) of 3.4–6.4 months. No standard second-line chemotherapy after GEM-platinum failure exists and data on survival benefit remain limited. Material and methods: We retrospectively reviewed patients with recurrent/advanced BTC who received gemcitabine-oxaliplatin (GEMOX)-based chemotherapy followed by 5-fluorouracil-irinotecan (FOLFIRI)-based chemotherapy to evaluate the efficacy of the sequential treatment strategy. Overall survival (OS) and PFS were calculated by Kaplan–Meier method. Results: Fifty-two patients were analyzed, 21 (40%) had intrahepatic, 14 (27%) had hilar/extrahepatic, and 17 (33%) had gallbladder cancer. Median age was 64 years (range 38–79 years). Prior curative intent resection of the primary tumor was performed in 23 (44.2%) patients and GEMOX adjuvant chemotherapy was given in 12 (23.1%) patients. After a median follow-up of 36.3 months, 47 (90.4%) patients completed the treatment strategy. First-sequence GEMOX and second sequence FOLFIRI achieved 4.8 months and 3.2 months median PFS, respectively. The global OS for the sequential chemotherapy was 21.9 months. The sequence of FOLFIRI resulted in a median OS of 8.4 months. Conclusion: The sequence of GEMOX-FOLFIRI is a potential treatment strategy for patients with recurrent/advanced BTC.